Revitalisasi Cinta Tanah Air dalam mengembangkan Moderasi Beragama - Ainah, Noor; Muhammad Hasan Said Iderus (Indonesian Journal of Islamic Religious Education, 2023)
Revitalizing patriotism is essential in building a religious moderation attitude among students. It focuses on building a healthy sense of nationalism and tolerance among religions, which is essential in strengthening diversity and unity in Indonesia. This research uses a qualitative approach with descriptive research methods. The research was conducted at Lambung Mangkurat University. This research used several data collection techniques, namely questionnaires, interviews, observation, and documentation. The research results show that most students, around 70%, strongly agree with revitalizing patriotism to develop moderate attitudes toward religion. This shows a strong understanding and positive acceptance of the importance of patriotism and moderation in religion. They recognize that patriotism and moderation in religion are two concepts that are interrelated and important for maintaining harmony and unity in Indonesia. This is a very good indicator that students at Lambung Mangkurat University are highly aware of the importance of patriotism and moderate attitudes toward religion.